Antonio degli Agli’s Defence of Immortality - Papiernik, Joanna (Renaissance and Reformation / Renaissance et Réforme, 2021)
In the article, the author briefly explains the popularity of the question of the immortality of the soul in the fifteenth century, presents the intellectual activity and bibliography of Antonio degli Agli, a prominent Tuscan humanist of the Quattrocento, and analyzes the content of Agli’s treatise On the Immortality of the Soul (De immortalitate animae). The short treatise remains only in manuscript and is rarely mentioned by scholars dealing with the history of the problem of immortality; however, it is a witness to the considerable popularity of the issue during the Renaissance. The article shows that the main arguments used by Agli relate to the metaphysics of light and the ontic affinity between the human mind and its most perfect objects of cognition. It is also demonstrated that these arguments largely coincide with those found in Marsilio Ficino’s opuscula theologica and the Platonic Theology.